Potensi Komik Web sebagai Media Edukasi Mental Health dan Self-Acceptance bagi Remaja Laki-laki di Indonesia - Setiawan, Kevin Christian; Aryani, Dewi Isma (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2023)
Understanding one's self-image or body image has long existed, but these concepts were previously thought to be only relevant to women. The truth is that guys can also have self-destructive thoughts. The complexity of body image issues is growing along with technology thanks to the existence of social media, which can affect users' thoughts and mental development, particularly in teens. Through the use of web comics, this research uses quantitative approach with a glass box methodology to educate and raise awareness about the problem of young boys' body-positivity and self-acceptance. The story's foundation was created by processing the findings of data collecting and analysis conducted through literature reviews, questionnaires, and interviews. Light and straightforward drawings are employed in the picture style to make it easier for readers to understand. It follows that this web comic can be utilized as a teaching tool about guys' self-acceptance so that they can be at peace with and accept themselves with all of their strengths and shortcomings.